Understanding the hierarchy of space on Traditional Malay houses: Rumah Kutai / Mohd Khazli Aswad Khalid ... [et al.] - Aswad Khalid, Mohd Khazli; Ahmad Zawawi, Zuraihana; Hashim, Hasnan; Abdullah Saleh, Alia; Sudirman, Mohd Dzulkarnaen (2021)
Space hierarchy and its importance in traditional Malay villages is a study done on the behavior of spatial humans and living space. It is a useful study as it allows for a better understanding of the relationship between human and environment. A review of the literature shows that a sense of privacy and its adaptation to social interactions in traditional Malay houses such as Kutai houses found along the Perak river can be determined by studying the house spatial arrangement, hardscape and softscape. THis is done by studying the appropriate dimensions for analysis and interpretation theory to be linked in the determination of transition space. In this study, using a quantitative method for the distribution of the components found in residential Malay houses, 18 Kutai houses were selected as a case study to determine the nature, function, and overall similarity for each sample. At the end of the study, the hierarchy of space in traditional Malay houses can be determined, i.e. starting with a public space which is followed by space, semi-public and semi-private spaces, and eventually, a private space. Transition spaces (semi-public, semi-private) in the neighborhood help residents manage the rate of social interaction and are therefore allowed to meet both the privacy and social relation needs of the residents.